Investigating the characteristics of various biomass applied to fuel-burning technologies - Ibraeva K. T.; Manaev Yu. O.; Khaustov S. A. Sergey Aleksandrovich; Tabakaev R. B. Roman Borisovich (Экоэнергетика, 2018)
Заглавие с экрана